Influence of parathyroid hormone on periodontal healing in animal models: A systematic review. (December 2020) - Stutz, Céline; Batool, Fareeha; Petit, Catherine; Strub, Marion; Kuchler-Bopp, Sabine; Benkirane-Jessel, Nadia; Huck, Olivier
Highlights: Parathyroid hormone has anabolic properties that may enhance periodontal healing. Parathyroid hormone decreased the inflammation induced by periodontitis. Intermittent administration of PTH is effective in periodontal healing in vivo. Abstract: Objectives: The purpose of this systematic review was to determine the potential interest of parathyroid hormone (PTH) as an adjunct to periodontal treatment based on studies performed in rodents. Materials & methods: Electronic databases (MEDLINE, Web of Science) were searched up to December 2019. Studies assessing the impact of PTH administration in experimental periodontitis in rodents have been identified. Results: Amongst the 247 identified articles, 10 met the inclusion criteria and were included in this systematic review. Experimental periodontitis was mainly induced by ligature placement or surgically with a dental bur. All studies considered bone healing after PTH administration at different frequencies as primary outcome. Results showed that an intermittent administration of PTH promoted bone healing and neovascularization. Nevertheless, a decrease of soft tissue inflammation was also observed. Conclusion: Intermittent administration of PTH appears to enhance significantly periodontal healing and to promote alveolar bone regeneration. However, due to the risk of side effects, the development of scaffolds allowing its local and time-controlled delivery is of importance.